Role of Documentation and Legal Information Network (JDIH) Efforts in Fulfillment of Human Rights - Dewi Sukmaningsih (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Indonesia is a country of law, and one of the characteristics of a state of law is the guarantee and protection of human rights, one of which is the right to obtain information, including the legal information that is information about the legislation both national and local. The principle of fiction (fictie) law states that any person considered to determine the existence of a legislation after its enactment, the ignorance of the people on the legislation, can not be excused. To that end, legislation information should be easily accessible. Issuance of Presidential Decree No. 33 of 2012 on Information and Documentation Network of National Law (JDIHN) isin order to fulfill the right to obtain legal information, especially information legislation. Management of Legal Documentation and Information Network by utilizing information and communication technology (ICT) makes legal information can be accessed quickly, easily, complete and accurate, thereby supporting the fulfillment of human rights, namely the right to obtain legal information properly.Keywords: Documentation and Legal Information Network, Efforts, Fulfillment, Human Rights